Laws, Statutes, Ordinances and Constitutions, Ordained, Made and Established, by the Mayor, Aldermen, and Commonalty, of the City of New York, Convened in Common-Council, for the Good Rule and Government of the Inhabitants and Residents of the Said City, at 11, , Ordinances of the City of New York § VI (1763) - (:unkn) unknown (General Publisher, 1763)
Prohibited the discharge of firearms in the City of New York
--
Keywords: DISCHARGE